2000
DOI: 10.1016/s0370-2693(00)00469-x
|View full text |Cite
|
Sign up to set email alerts
|

Moduli constraints on primordial black holes

Abstract: Abstract. The amount of late decaying massive particles (e.g., gravitinos, moduli) produced in the evaporation of primordial black holes (PBHs) of mass M BH < ∼ 10 9 g is calculated.Limits imposed by big-bang nucleosynthesis on the abundance of these particles are used to constrain the initial PBH mass fraction β (ratio of PBH energy density to critical energy density at formation), as: β < ∼ 5 × 10 −19 (x φ /6 10 −3 ) −1 (M BH /10 9 g) −1/2 (Y φ /10 −14 ); x φ is the fraction of PBH luminosity going into grav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…While PBH reheating has been considered [29,30], it can be shown that [31,32,33] that the period of PBH domination necessary would lead to the overproduction of (supersymmetric) moduli fields and gravitinos upon their evaporation that contradict the predictions of big bang nucleosynthesis (BBN). While the authors of [28] seem to confuse the distinction between radiation perturbations and PBH perturbations (see their Equation (11)), we show later that PBH merging could be a natural consequence of clustering.…”
Section: A Pbh Clusteringmentioning
confidence: 99%
“…While PBH reheating has been considered [29,30], it can be shown that [31,32,33] that the period of PBH domination necessary would lead to the overproduction of (supersymmetric) moduli fields and gravitinos upon their evaporation that contradict the predictions of big bang nucleosynthesis (BBN). While the authors of [28] seem to confuse the distinction between radiation perturbations and PBH perturbations (see their Equation (11)), we show later that PBH merging could be a natural consequence of clustering.…”
Section: A Pbh Clusteringmentioning
confidence: 99%
“…A PBH radiates any and all particles whose rest mass is substantially less than its current temperature, including gravitons. If the PBH radiate massive, long-lived particles one obtains tight bounds on their initial population [10,11,12,13,14] but these limits are contingent upon assumptions about particle physics and quantum gravity, and other radiated particles will reach thermal equilibrium, erasing any memory of their origin. However gravitons emitted as the black hole decays cannot equilibriate and will always survive until the present day, producing a stochastic background of gravitational waves.…”
mentioning
confidence: 99%
“…Following References [1,2,98,180] and [183,184] (but in a different framework and using more stringent constraints), limits on the mass fraction of black holes at the time of their formation (β ≡ ρ PBH /ρ tot ) were derived in Reference [185] using the production of gravitinos during the evaporation process. Depending on whether gravitinos are expected to be stable or metastable, the limits are obtained using the requirement that they do not overclose the universe and that the formation of light nuclei by the interactions of 4 He nuclei with nonequilibrium flux of D,T, 3 He and 4 He does not contradict the observations.…”
Section: Pbh Evaporation As Universal Particle Acceleratormentioning
confidence: 99%